Sistem Pakar Diagnosa Penyakit Berisiko Di Setiap Status Gizi Berdasarkan Indeks Massa Tubuh Menggunakan Metode Hy-brid Case Base - Pratama, Rifqhy Rayhan Andi Riga; Norhikmah, Norhikmah (Faktor Exacta, 2023)
Nutritional status is an indicator of health for a person which is divided into four classifications, namely, Obesity, Overweight, Normal Weight, and Underweight. and nutritional status can be obtained by calculating the body mass index (BMI) of the person by dividing the body weight (kg) by the height (m2). after knowing the nutritional status, a diagnosis can be made by applying the Hybrid Case Base method. Applicationing of this method is too precise because it can provide accurate diagnostic results because this method combines two methods, namely Case Based Reasoning and Rule Based Reasoning. With this expert system, it can help people to find out their nutritional status and whether they have a risky disease or not, especially for people who don't have a lot of free time to consult with doctors so they can do it only by using the expert system that has been created. This method is quite fast and practical and provides accurate diagnostic results as well.